2020
DOI: 10.1093/mnras/staa1304
|View full text |Cite
|
Sign up to set email alerts
|

Black widow evolution: magnetic braking by an ablated wind

Abstract: Black widows are close binary systems in which a millisecond pulsar is orbited by a companion, a few per cent the mass of the sun. It has been suggested that the pulsar’s rotationally powered γ-ray luminosity gradually evaporates the companion, eventually leaving behind an isolated millisecond pulsar. The evaporation efficiency is determined by the temperature Tch ∝ F2/3 to which the outflow is heated by the flux F on a dynamical time-scale. Evaporation is most efficient for companions that fill their Roche lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…As an example, we consider the case of gamma-ray ablation. If we assume the gamma-ray luminosity is 10% of the spin-down luminosity ( 3×10 35 erg s −1 based on our long-termν measurement) as typically seen in black widow systems (Abdo et al 2013), this would imply a companion mass loss rate of ∼ 10 −11 M /yr (Ginzburg & Quataert 2020). For a source distance of 8 kpc and assuming that gravitational wave losses dominate in Equation 4, this implies β ≈ 0.04 and α ≈ 0.4, suggesting that the mass ejection occurs somewhere between the pulsar and the L 1 point (α ≈ 0.8).…”
Section: ∆ω 4πmentioning
confidence: 96%
See 2 more Smart Citations
“…As an example, we consider the case of gamma-ray ablation. If we assume the gamma-ray luminosity is 10% of the spin-down luminosity ( 3×10 35 erg s −1 based on our long-termν measurement) as typically seen in black widow systems (Abdo et al 2013), this would imply a companion mass loss rate of ∼ 10 −11 M /yr (Ginzburg & Quataert 2020). For a source distance of 8 kpc and assuming that gravitational wave losses dominate in Equation 4, this implies β ≈ 0.04 and α ≈ 0.4, suggesting that the mass ejection occurs somewhere between the pulsar and the L 1 point (α ≈ 0.8).…”
Section: ∆ω 4πmentioning
confidence: 96%
“…These are motivated by the study of rotation-powered radio millisecond pulsars in detached (non-accreting) binaries: the so-called "black widow" (M c 0.05M ) and "redback" (M c 0.1M ) systems, where M c is the companion mass (see, e.g., Romani et al 2016, and references therein). One possibility is black-widow-like ablation of the companion, driven by rotation-powered gamma-ray emission from the pulsar (Ginzburg & Quataert 2020). Such ablation could also be driven by particle heating via the rotation-powered pulsar wind (see Harding & Gaisser 1990, and references therein).…”
Section: ∆ω 4πmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is reasonable to assume that a captured, puffedup MS star can transfer mass to a NS and spin it up to a MSP. However, CMC currently lacks detailed treatments of MS stars in tidal capture interactions, and COSMIC does not include the latest pulsar physics such as pulsar irradiation (e.g., Chen et al 2013;Ginzburg & Quataert 2020, and references therein). We will consider these details and study model MSPs and tidal-captured NS-MS star binaries that overlap with the observed pulsar binaries in future works.…”
Section: Pulsarsmentioning
confidence: 99%
“…Spinorbit coupling relies on the presence of a variable mass quadrupole in the companion star (Applegate & Shaham 1994;Richman et al 1994), however, a low-mass companion likely does not have a sufficient energy budget for this mechanism (Brinkworth et al 2006), which is only exacerbated for IGR J17062, which has the smallest known mass function among stellar binaries (Strohmayer et al 2018). Enhanced magnetic braking might play a role (Justham et al 2006;Ginzburg & Quataert 2020), but only if the companion star can sustain a ∼ 1 kG magnetic field and is also losing mass through a stellar wind. In the following, we therefore limit our discussion to just the mass loss model.…”
Section: Binary Evolutionmentioning
confidence: 99%